Engineering design: an approach to the development creativity - Hawlader, Mohammad Nurul Alam (IIUM Press, 2011)
In a competitive world with limited resources, it is important to train our students in creativity. To maintain an edge over others, it is essential to produce unusual solutions to problems and challenges. Training students in divergent thinking is considered an essential element in the development of creativity. Ideas, whatever the nature may be, must be respected and encouraged. Engineering design enables students to be trained in creativity. Torrance tests provide a measure of originality, fluency, flexibility and elaboration.